Étude métallographique de fers à cheval et d’outillage agricole du site de Montbaron. Éléments de réflexion sur la qualité des matériaux employés en sidérurgie médiévale - Delphine Neff; Philippe Dillmann; Maxime Lheritier; Armelle Querrien (Archéologie Médiévale)
Analysis of the constitution and structure of the metal composing horseshoes and agricultural tools from Montbaron has provided information on the processes of obtaining the metal, as well as on its use. The six objects analysed were made from billets containing steel, iron and phosphorous iron. Two of them, a hatchet and a hoe, seem to have undergone case hardening or treatment intended to render their external surfaces more resistant. The ard ploughshare and the horseshoes however do not show, in their minor elements, a homogenous composition : the original billets have not been deliberately chosen for any specific qualities. The presence of a high phosphorous content implies the use of a phosphorous iron ore, considered hitherto as not being exploitable during the Middle Ages.